Comparison of the antimicrobial consumption in weaning pigs in Danish sow herds with different vaccine purchase patterns during 2013. Issue 1 (December 2016) - Temtem, Carolina; Kruse, Amanda; Nielsen, Liza; Pedersen, Ken; Alban, Lis
Abstract Background There is growing concern about development of antimicrobial resistance due to use of antimicrobials (AMs) in livestock production. Identifying efficient alternatives, including vaccination, is a priority. The objective of this study was to compare the herd-level amount of AMs prescribed for weaner pigs, between Danish sow herds using varying combinations of vaccines against Porcine Circovirus Type 2 (PCV2), Mycoplasma hyopneumoniae (MYC) andLawsonia intracellularis (LAW). It was hypothesised that herds purchasing vaccines, use these to prevent disease, and hence reduce their AM consumption, compared to herds purchasing fewer or no vaccines against these pathogens. Data summarised over year 2013 were obtained from the Danish Central Husbandry Register and the Danish VetStat database, in which prescriptions of medication are recorded. All one-site indoor pig herds with >50 sows and >200 weaners were selected. AMs prescribed for weaners was measured in animal daily doses (ADD) and divided according to three indication groups (gastro-intestinal, respiratory indication or total use). The analysis was based on three multivariable linear regression models of the herd-level ADD for each indication group. The eight vaccination combinations (2x2x2) were included as one explanatory variable, and herd size, measured as the number of weaner pen places was included in the models as a potential confounder. Results Out of the 1513 herds in the study, 1415 had AMs prescribed for gastro-intestinal disorders, and 836 for respiratory disorders. PCV2 vaccines were purchased in 880 herds, MYC vaccines in 787 and LAW vaccines in 115 herds. Herds purchasing PCV2 and MYC vaccines had significantly more AMs prescribed than herds not purchasing vaccines or only purchasing LAW vaccines. Conclusion In the present study, using register data covering 1 year, we found an association between use of vaccination and increased amount of AMs prescribed for weaners. This does not exclude that the vaccines work, just that we were unable to detect this. The findings might be explained by some herds experiencing clinical problems associated with MYC or PCV2 despite use of vaccination. In other herds, it might reflect that vaccines applied to weaners are used for disease prevention in finishers rather than in the weaners. Information about vaccination protocols and herd health status was not available at the time of the study. Hence, further studies are required to investigate causality of the associations between use of AMs, vaccination practices and other confounding on-farm factors.